2017
DOI: 10.1038/s41598-017-10218-z
|View full text |Cite
|
Sign up to set email alerts
|

Chemical synthesis of hierarchical NiCo2S4 nanosheets like nanostructure on flexible foil for a high performance supercapacitor

Abstract: In this study, hierarchical interconnected nickel cobalt sulfide (NiCo2S4) nanosheets were effectively deposited on a flexible stainless steel foil by the chemical bath deposition method (CBD) for high-performance supercapacitor applications. The resulting NiCo2S4 sample was characterized by X-ray powder diffraction (XRD), field emission scanning electron microscopy (FE-SEM), high-resolution transmission electron microscopy (HR-TEM), and electrochemical measurements. XRD and X-ray photoelectron spectroscopy (X… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(15 citation statements)
references
References 56 publications
0
15
0
Order By: Relevance
“…0.33, 0.34, and 0.36 nm, respectively, similar to those reported by Kim and Liang for NiCo 2 S 4 . 63,64 The BET surface areas were similar for NC13, NC11, and NC31, at ca.15, 12, and 16 m 2 g −1 , respectively. 63 The composition and chemical valence states of the nickel cobalt sulfides were characterized by X-ray photoemission spectroscopy (XPS), confirming the presence of cobalt, nickel, and sulfur in all three samples.…”
Section: Physical Characterizationmentioning
confidence: 91%
“…0.33, 0.34, and 0.36 nm, respectively, similar to those reported by Kim and Liang for NiCo 2 S 4 . 63,64 The BET surface areas were similar for NC13, NC11, and NC31, at ca.15, 12, and 16 m 2 g −1 , respectively. 63 The composition and chemical valence states of the nickel cobalt sulfides were characterized by X-ray photoemission spectroscopy (XPS), confirming the presence of cobalt, nickel, and sulfur in all three samples.…”
Section: Physical Characterizationmentioning
confidence: 91%
“…It can be clearly seen from the CV curves in Figure 6b that FeNiS showed the highest area under CV curves at 2 mV/s compared to FeNiO and NF, leading to higher capacitance values. The capacitance increases with decreasing scan rates, which could be due to sufficient time provided for the faradic reaction representing the pseudocapacitive behavior ( Figure S5a) [43,44]. The results of the galvanostatic charge-discharge test are represented by the relationship between specific capacitance with respect to the current density in Figure 6c.…”
Section: Resultsmentioning
confidence: 97%
“…In our study, the FeNiS showed a performance with 77.3% retention after 5000 cycles in charge-discharge measurements and comparable capacitance results to several other reports (Table S4 and Figure S5c). behavior ( Figure S5a) [43,44]. The results of the galvanostatic charge-discharge test are represented by the relationship between specific capacitance with respect to the current density in Figure 6c.…”
Section: Resultsmentioning
confidence: 99%
“…Closer examination of some of the crystals of chromium-(NC11 Cr), manganese-(NC11 Mn), and iron-doped (NC11 Fe) samples, revealed d-spacings of the (440) planes of 0.30, 0.32, and 0.30 nm (AE0.1 nm), respectively; these are similar to values that Kim and Liang reported in the literature for NiCo 2 S 4 . 57,58 Energy-Dispersive (X-ray) Spectroscopy (EDS) mapping ( Fig. S3 †) suggested that the dopant cations were evenly distributed across the near-surface of the cobalt-nickel sulde samples.…”
Section: Physical Characterizationmentioning
confidence: 99%